The Role of Pesantren in Islamic Education Management: A Systematic Review of Human Resource Development and Community Empowerment - Rizma Ilfi; Siti Amanah; Arif Satria; Jaenal Effendi (Attractive : Innovative Education Journal, 2026)
This study aims to analyze the strategic role of pesantren in Islamic education management, with a particular focus on human resource development and local community empowerment. Using a systematic literature review, this Research synthesizes peer-reviewed articles indexed in reputable international and national databases, following the PRISMA protocol to ensure methodological rigor and transparency. The data were collected through a structured screening and eligibility process, resulting in the selection of relevant studies that examine pesantren from educational, managerial, social, and economic perspectives. The findings indicate that pesantren have evolved into adaptive Islamic education organizations that integrate spiritual values with modern management practices, enabling them to contribute significantly to human resource capacity building and sustainable community empowerment. Moreover, pesantren demonstrate managerial flexibility in responding to contemporary challenges, including socio-economic transformation and educational disruption. The study highlights that religious values function not as constraints but as institutional resources that strengthen organizational resilience and community-oriented initiatives. These results contribute to the advancement of Islamic education management theory by positioning pesantren as value-driven institutions with strategic relevance for sustainable human development and community-based empowerment